Carbonate chemistry speciation of the 2023 KOSMOS Helgoland experiment on the effects of ocean alkalinity enhancement on pelagic foodwebs - Kai Georg Schulz; Julieta Schneider; Ulf Riebesell (PANGAEA, 2025)
This dataset contains carbonate chemistry speciation data of the 2023 KOSMOS mesocosm study on Helgoland, Germany. This study tested the effects of ocean alkalinity enhancement simulating lime additions on pelagic ecosystem functioning during a spring bloom. Carbonate chemistry speciation (fCO2, pHT, calcium carbonate saturation state) was generally calculated from measurements of total alkalinity (TA) and dissolved inorganic carbon (DIC) in depth-integrated water samples. There were 12 mesocosms in total and in 6 of them an alkalinity gradient of up to +1250 umol/kg was established in steps of 250 umol/kg. In the remaining 6 the same amount of alkalinity was added only to the upper portion of the mesocosms, resulting in twice the alkalinity increase there, before being mixed in after 48 hours. The two treatments simulated the immediate dilution of TA after ship deployment as well as a delayed one from a point source.